2021
DOI: 10.1038/s41582-021-00589-3
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease in African American individuals: increased incidence or not enough data?

Abstract: Research on racial differences in Alzheimer disease (AD) dementia has increased in recent years. Older African American individuals bear a disproportionate burden of AD and cognitive impairment compared with non-Latino white individuals. Tremendous progress has been made over the past two decades in our understanding of the neurobiological substrates of AD. However, owing to well-documented challenges of study participant recruitment and a persistent lack of biological data in the African American population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 90 publications
1
79
0
Order By: Relevance
“… 49 Much larger longitudinal studies of diverse cohorts are needed to evaluate the intersection of race, AD biomarkers, cognitive impairment, medical comorbidities, and social determinants of health. 50 Improved understanding of these complex factors will enable more accurate AD diagnosis and improve patient care for all groups.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Much larger longitudinal studies of diverse cohorts are needed to evaluate the intersection of race, AD biomarkers, cognitive impairment, medical comorbidities, and social determinants of health. 50 Improved understanding of these complex factors will enable more accurate AD diagnosis and improve patient care for all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle, exercise, diet, and environmental factors also appear to influence BDNF signaling and thus appear to play a role in AD ( Pistollato et al, 2018 ). High prevalence in the geriatrics population of African American and Japanese origin points toward the role of lifestyle as a risk/contributory factor in AD ( Barnes, 2022 ). Animal models have reported that chronic stress and sedentary lifestyle negatively influence BDNF signaling ( Perna and Brown, 2013 ; Vassoler et al, 2013 ).…”
Section: Lifestyle Diet Drugs and Bdnf Levelsmentioning
confidence: 99%
“…The majority of research has been conducted in clinical trials or clinical research settings using CSF biomarkers of AD and the vast majority of participants have been non-Hispanic Whites (NHWs). Although Hispanic and African American (AA) communities have significantly higher rates of dementia (16) and therefore may gain significant benefit from the use of AD biomarkers in clinical assessment, there is limited research on blood-based biomarkers of AD in these communities (4,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%